Shakespeare’s Linguistic Turn in King Lear - McKenna, Andrew J. (Anthropoetics, 2019)
Loyola University Chicago[1] amckennluc.edu Richard van Oort’s Shakespeare’s Big Men: Tragedy and the Problem of Resentment affords a productive encounter between René Girard’s mimetic theory and Eric Gans’s generative anthropology, where the center/periphery structure is the model of cultural origins and subsequent organization. Lear’s abdication of the royal center precipitates a lethal mimetic vortex all along...